Importance of the Positive-Strand RNA Secondary Structure of a Murine Coronavirus Defective Interfering RNA Internal Replication Signal in Positive-Strand RNA Synthesis - Repass, John F. (American Society for Microbiology, 1998)
The RNA elements that are required for replication of defective interfering (DI) RNA of the JHM strain of mouse hepatitis virus (MHV) consist of three discontinuous genomic regions: about 0.46 to 0.47 kb from both terminal sequences and an internal 58-nucleotide (nt)-long sequence (58-nt region) present at about 0.9 kb from the 5′ end of the DI genome. The internal region is important for positive-strand DI RNA synthesis (Y. N. Kim and S. Makino, J. Virol. 69:4963–4971, 1995). We further characterized the 58-nt region in the present study and obtained the following results. (i) The positive-strand RNA structure in solution was comparable with that predicted by computer modeling. (ii) Positive-strand RNA secondary structure, but not negative-strand RNA structure, was important for the biological function of the region. (iii) The biological function had a sequence-specific requirement. We discuss possible mechanisms by which the internal cis-acting signal drives MHV positive-strand DI RNA synthesis.